Du Pont System Analysis in Goods Consumption Companies Listed on The Indonesian Stock Exchange 2018-2022 - Safitri, Alia; Sulaksono, Erika Dwi; Firmansyah, Muhammad; Sunardi, Nardi (Indonesian Development of Economics and Administration Journal, 2024)
This research aims to determine the financial performance of Consumer Goods companies listed on the Indonesia Stock Exchange for the 2018-2022 period using Du Pont analysis. The results of this research show that the company PT Gudang Garam Tbk has an average value of 6.24% smaller than 8.23% categorized as performing less well, PT Indofood CBP Sukses Makmur Tbk average value of 8.61% is greater than 8.23% categorized as performing well, PT Kalbe Farma Tbk average value of 8.58% is greater than 8.23% categorized Good performance, PT Mayora Indah Tbk average value of 7.31% is smaller than 8.23% categorized as poor performance, PT Ultra Jaya Milk Industri Tbk average value of 10.41% is greater than 8.23% is categorized as performing Good. By using Du Pont system analysis on Consumer Goods companies listed on the Indonesia Stock Exchange for the 2018-2022 period, an average value of 8.23% was obtained. This shows that overall financial performance is said to be good performing.